Thermal decomposition and stability in a series of tetrafluorborate copper(I) complexes - de Lucca Neto, V. A.; Mauro, Antonio Eduardo [UNESP]; Sargentelli, V.; Ionashiro, Massao [UNESP] (Elsevier, 1995)
Tetrafluorborate copper(I) complexes containing acetonitrile, triphenylphosphine, 1,10-phenanthroline, 2,2′-bipyridine and 2-quinolinethiol have been prepared in order to study their thermal stabilities as a function of the ligands present. The characterization of the above compounds was carried out by elemental analysis and IR spectroscopy. Their thermal behaviour has been investigated and the final products were identified by X-ray powder diagrams. © 1995.
Keywords: Copper; Infrared spectroscopy; Tetrafluorborate; Thermal analysis